THE INGGRISAN SITE AS A MEDIUM AND SOURCE FOR HISTORY LEARNING IN PUBLIC SENIOR HIGH SCHOOLS IN BANYUWANGI REGENCY: SITUS INGGRIASAN SEBAGAI MEDIA DAN SUMBER BELAJAR SEJARAH SMA NEGERI DI KABUPATEN BANYUWANGI - Mahfud; Nurul Aisyah; I Kadek Yudiana (SOSIOEDUKASI, 2025)
This study aims to analyze the utilization of the Inggrisan Site as a medium and source for history learning at the senior high school (SMA) level in Banyuwangi Regency. The background of this study is rooted in the importance of integrating local historical values into history education to strengthen students' historical identity and literacy. This research employs a descriptive qualitative approach, with data collection techniques including in-depth interviews, participatory observation, and documentation. The research informants consist of history teachers, students, local figures, and site managers. Data validation is conducted through source and technique triangulation. The findings reveal that the Inggrisan Site holds significant potential as a contextual learning resource, yet it has not been optimally utilized in history education practices. The main challenges identified include the limited accommodation of local history content in the curriculum, the lack of teacher capacity in utilizing historical sites, and the insufficient availability of site-based teaching materials. On the other hand, development opportunities arise from the support of the Merdeka Curriculum policy, the potential for cross-sectoral collaboration, and advances in educational technology that enable the digitization of heritage sites as learning media. This study recommends the need to strengthen synergy among educational institutions, local government, and cultural communities in developing a sustainable, site-based history learning model.